Spiritual Well-Being, Social Support, and Financial Distress in Determining Depression: The Mediating Role of Impact of Event During COVID-19 Pandemic in Iran - Sharif Nia, Hamid; Gorgulu, Ozkan; Naghavi, Navaz; Robles-Bello, María Auxiliadora; Sánchez-Teruel, David; Khoshnavay Fomani, Fatemeh; She, Long; Rahmatpour, Pardis; Allen, Kelly-Ann; Arslan, Gokmen; Pahlevan Sharif, Saeed (Frontiers in Psychiatry, 2021)
This study investigates the relationship between spiritual well-being, social support, and financial distress with depressive symptoms due to the COVID-19 pandemic. A path analysis was used to analyze data collected from 1,156 Iranian participants via an online survey. The results showed that spiritual well-being and social support were negatively related to depressive symptoms and financial distress. The impact of COVID-19 events showed negative associations with depressive symptoms. In addition, the link between spiritual well-being and financial distress with depressive symptoms was partially mediated by the impact of events.